In vitro metabolism of different cellulosic feeds by Ruminococcus albus pure culture - KUMAR, SHIV; SANGWAN, D C; SINGH, SADHANA; BHATIA, S K; DULAR, R K (The Indian Journal of Animal Sciences, 2014)
Rumen metabolic activity in vitro by Ruminococcus-albus (cellulolytic bacteria isolated from buffalo) on nutritively variable cellulosic substrates (CP 2.1 to 20.3%, NDF 50.3 to 77.7%, cellulose 26.5 to 39.7%) was profiled. Standard batch culturing technique for different time course (12, 24, 48, 72 and 96 hr) fermentation of 9 substrates like wheat straw, paddy straw. pearlmillet stover, sorghum stover and berseem hay (group 1) and chkkpca straw, sugarcane bagasse, oathay and alfalta hay (group 2) was followed. Concentration of ruminal nitrogen fractions (barring protein-N which continually elevated up to 96 hr) increased (P